Analyzing occupational challenges through the lens of body and biography. Issue 2 (3rd April 2018) - Carandang, Kristine; Pyatak, Elizabeth A.
ABSTRACT: Introduction: Occupational scientists are tasked with the responsibility of examining the relationship between occupational engagement and health, yet as occupations are explored in situ, these concepts only become more complex. For example, lifestyle trade-offs occur when individuals make conscious decisions between two competing sets of actions: actions taken in promotion of physical health versus actions in agreement with an identity-driven biography. In this study, these dilemmas are viewed as parts of an ongoing occupational challenge to balance physical health with subjective well-being in everyday life. Methods: Anselm Strauss's concepts of body state and biographical moment are conceptualized as analytic tools to study dimensions within which occupation is performed. A descriptive, single-case analysis of a young adult diagnosed with diabetes is presented as an exemplar of how Strauss's tools may be utilized. Results: Four themes emerged within the presented narrative: (1) by the book versus reality, (2) testing the boundaries of diabetes, (3) diabetes burnout and the struggle for perfection, and (4) the inevitable merge between body and biography. Conclusion: Sadie's narrative exemplifies the multiple contexts in which agentic decisions to engage in specific occupations are made. Sadie's experiences of diabetes burnout and actions taken while "on vacation" are not uncommon within chronic illness literature and warrant further analyses that consider physical and psychological domains of health. By dismantling situational factors using analytic tools, such as Strauss's body state and biographical moment, occupational scientists may further understand lived experiences and clarify the link between occupation and health.